STRATEGY OF FOOD TOLERANCE DEVELOPMENT IN CHILDREN WITH FOOD ALLERGY - G. A. Novik (Вопросы современной педиатрии, 2015)
Food tolerance development is a key factor in treatment and prevention of food allergy in children. This paper focuses on factors contributing to the tolerance development, immunological mechanisms of food tolerance development, and possibilities of food allergy prevention. The tactics for complimentary food introduction in children with food allergy are also considered. The mechanism of a preventive effect of partially hydrolyzed milk formulas is analyzed. Based on the literature review, the importance of probiotics and prebiotics in food tolerance development is determined. It is shown that better understanding of underlying mechanisms involved in the development of tolerance to staple food may decrease the time needed to achieve remission of a large variety of food allergy in children and individualize the elimination diet.